Sweater weather - Phelan, Matt 1970-
"On a crisp, fall day and evening, rambunctious bear cubs turn getting dressed into an adventure"--
Keywords: Sweaters / Juvenile fiction; Bears / Juvenile fiction; Autumn / Juvenile fiction; Sweaters / Fiction; Bears / Fiction; Autumn / Fiction; Chandails / Romans, nouvelles, etc. pour la jeunesse; Ours / Romans, nouvelles, etc. pour la jeunesse; Automne / Romans, nouvelles, etc. pour la jeunesse; JUVENILE FICTION / General; Bears; Autumn; Sweaters; Picture books for children; Picture books; picture books; Stories in rhyme; Animal fiction; Fiction; Juvenile works; Children's stories / Pictorial works; Livres d'images; Histoires rimées; Bilderbuch